Malawi : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
According to MGDS-II, certain major factors such as Malawi's vulnerability to external shocks, inadequate policy response, and weak implementation capacity have hindered growth and development of the economy. The political risks resulting from the upcoming 2014 tripartite elections have also been cited as a major issue. The report suggests that the government should look into the issues of corruption. IMF staffs has put forth certain guidelines that need to be followed when the first Annual Progress Report is prepared.